NATIONAL SOCIAL INVESTMENT PROGRAMME (N-SIP), VULNERABLE POPULATIONS AND SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN ENUGU STATE, NIGERIA: TRACING A NEXUS - ONAH, F. N; ANIKWE, S. O.; ONAH, FAB O. (International Journal of Psychosocial Rehabilitation, 2021)
The National Social Investment Programme (N-SIP) of Nigeria is a social welfare initiative created by the Federal Government in 2015 to ensure equitable distribution of resources to vulnerable populations to address, hunger, poverty and well-being which incidentally are the first three Sustainable Development Goals. In spite of the huge N-SIP annual budget, the well-being of vulnerable populations has not shown any satisfactory improvement. The main goal of this study was to trace the impact of N-SIP on SDGs 1, 2 and 3 in Enugu State, Nigeria. The specific objectives are to; (a) find out the impact of Conditional Cash Transfer of N-SIP on poverty and well-being of vulnerable populations in Enugu State; (b) examine the effectiveness of the home-grown school feeding programme in Enugu State and (c) find out the obstacles impeding the success of N-SIP. The study used a multi-dimensional approach which includes visits to a sample of the 421 Communities in Enugu State, documentary evidence, interviews with key informants (KIs) in relevant ministries and Focus Group Discussions. The findings were analyzed and discussed based on sustainable development theory which is the study’s theoretical platform. The less than satisfactory impact of NSIP on poverty and hunger of vulnerable populations in Enugu State was demonstrated. The paper argues that N-SIP lacked focus, predicated on imaginary data and unsustainable. We ended the paper by packaging some proactive policy intervention measures including putting more efforts in data banking and management.